1972
DOI: 10.1111/j.1365-2222.1972.tb01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic infertility: laboratory techniques to detect antispermatozoal antibodies

Abstract: Twenty sera from fertile and infertile women were examined for antibodies to spermatozoa or to semitial plasma, to determine which of the five techniques tested provided reliable evidence of allergic infertility.Ten sera agglutinated seminal plasma coated tanned red cells, six agglutinated spermatozoa, ten gave mixed cell antiglobulin agglutination and fourteen gave immunofiuorescent reactions for IgG or igM antispermatozoal antibodies, and three were cytotoxic to sperm.The results of tests for seminal plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1973
1973
1988
1988

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…The close correlation between immobilizing and agglutinating activity has been found previously by several workers (Alexander et al 1974, Husted 1975, Husted & Inverslev 1975, Samuel et al 1975, Quinlivan et al 1975. Some of our agglutinating or immobilizing sera had no immuofluorescent antibody, and in fact poor or absent correlation of agglutinating and immobilizing activity with the immunofluorescent test has been reported repeatedly (Feltkamp et al 1965, Hjort & Hansen 1971, Jeffery & Parish 1972, Jones & Ing 1974, Boettcher 1974, Husted 1975. It has been suggested by Rumke (1974) that this lack of correlation is due to the involvement of different antigens in the immobilizing and agglutinating tests (which are directed against surface antigens) and the immunofluorescent test (apparently directed against sub-surface antigens).…”
Section: Discussionmentioning
confidence: 69%
“…The close correlation between immobilizing and agglutinating activity has been found previously by several workers (Alexander et al 1974, Husted 1975, Husted & Inverslev 1975, Samuel et al 1975, Quinlivan et al 1975. Some of our agglutinating or immobilizing sera had no immuofluorescent antibody, and in fact poor or absent correlation of agglutinating and immobilizing activity with the immunofluorescent test has been reported repeatedly (Feltkamp et al 1965, Hjort & Hansen 1971, Jeffery & Parish 1972, Jones & Ing 1974, Boettcher 1974, Husted 1975. It has been suggested by Rumke (1974) that this lack of correlation is due to the involvement of different antigens in the immobilizing and agglutinating tests (which are directed against surface antigens) and the immunofluorescent test (apparently directed against sub-surface antigens).…”
Section: Discussionmentioning
confidence: 69%
“…This supports the statement by Southam (1963) that though thirty-one sera agglutinated cells coated with seminal plasma, only three agglutinated cells coated with sperm extracts. Moreover, Jeffery & Parish (1972) found that results of tests for agglutinins to seminal plasma were unrelated to results of tests detecting antibodies to spermatozoa by agglutination, mixed-cell antiglobulin, immunofluorescence and cytotoxic tests. A non-antibody spermagglutinating substance has been detected by fractionation of one human serum (Boettcher & Kay, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were also obtained from seven women who were virgo intacta. Tanned cell agglutination test for antibodies to seminal plasma Seminal plasma was adsorbed to the surface of human Group O red cells by the method of Boyden (1951) as modified by Jeffery & Parish (1972). Seminal plasma was obtained from blood Group O men, or from non-secretor group A and men and demonstrated to contain no A or antigen by its failure to reduce the titre of anti-A or anti-B red cell agglutinins.…”
Section: Seramentioning
confidence: 99%
“…Antigen for the lymphocyte tests was sterilized with a millipore syringe filter before use, Immunoglobuiin assays and antibody determinations Total immunoglobulins G, M and A were assayed by radial immunodifl'usion plates. Total IgE was assayed by Phadebas PRIST, Antibodies to suspensions of dead, washed, spermatozoa, and to seminal plasma by the tanned-cell agglutination test were done by the methods of Jefl'ery and Parish (1972), Agglutinating antibody to the seminal-plasma allergenic fraction was determined by the red-cell-linked antigen-antiglobulin reactions (RCLA-AR) of Coombs et al (1965) and Hunter and Coombs (1969) as modified by Parish (1969), Rabbit IgG anti-human group O red cells was reduced and reconstituted in a univalent 7S form. The antibody was mixed with the seminal-plasma antigen fraction in the approximate ratio of 1:2 mol, and coupled with bis-diazo-benzidine (BDB) in the ratio of 1 mol total protein:4-5 mol BDB, After treatment for 6 hr at 0°C, the coupled antibody was dialysed against saline pH 7 2 and purified by filtration down a Sephadex G200 column.…”
Section: Preparation Of Antigen and Allergenic Fractionmentioning
confidence: 99%